STUDI FENOMENOLOGI MAKNA HIDUP PASIEN SKIZOFRENIA - Dhiyarunnisa Shabrina; Nio, Suci Rahma (CAUSALITA : Journal of Psychology, 2023)
The meaning of life is something that gives special value to an individual so that it becomes the goal of life. The process to achieve the meaning of life consists of components that form the basis for consideration of whether a person can be considered successful in his life. Nurses of schizophrenia patients who work to care for and look after patients have the right to choose their goals in life. This is useful as a basis for whether he can be seen as having value in his life and being able to achieve goals and meaning in his life. Schizophrenia disorder is a condition of abnormalities in the neurobiology of the brain resulting in hallucinations and delusions, impaired focus, impaired thinking and problem solving, and difficulties in interacting. This research aims to find out the meaning of life for a nurse with schizophrenia. The research method used is a qualitative method using a phenomenological approach with data triangulation analysis techniques. The subjects in this study consisted of three nurses for schizophrenia patients at the Social Rehabilitation Home, Pelita Jiwa Insani Foundation, Padang City. This study used a semi-structured interview technique using an interview guide as a data collection method. The results of this study are that of the three research respondents involved, it is known that all respondents have been able to interpret their lives as nurses for schizophrenic patients.